Band gap modulation of zirconium-based metal-organic frameworks by defect engineering - Marco Taddei (Journal of Materials Chemistry A, 2019)
We report a defect-engineering approach to modulate the band gap of zirconium-based metal-organic framework UiO-66, enabled by grafting of a range of amino-functionalised benzoic acids at defective sites. Defect engineered MOFs were obtained by both post-synthetic exchange and modulated synthesis, featuring band gap in the 4.1-3.3 eV range. First principle calculations suggest that shrinking of the band gap is likely due to an upward shift of the valence band energy, as a result of the presence of light-absorbing monocarboxylates. The photocatalytic properties of defect-engineered MOFs towards CO2 reduction to CO in the gas phase and degradation of Rhodamine B in water were tested, observing improved activity in both cases, in comparison to a defective UiO-66 bearing formic acid as the defect-compensating species.